2000
DOI: 10.1007/s002670010085
|View full text |Cite
|
Sign up to set email alerts
|

How Well Does Brazil's Environmental Law Work in Practice? Environmental Impact Assessment and the Case of the Itapiranga Private Sustainable Logging Plan

Abstract: / The Itapiranga Sustainable Logging Plan provides an example of how Brazil's licensing system functions for logging companies in the state of Amazonas. Two questions need to be dealt with: "How sustainable can logging in the Amazon be?" and "What and how effective are existing legal mechanisms to deal with logging projects?" The environmental impact assessment (EIA) and environmental impact statement (EIS, known as the RIMA in Brazil), present relatively detailed accounts of biodiversity and the need to adopt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
3

Year Published

2002
2002
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 20 publications
0
7
0
3
Order By: Relevance
“…Although the increase in certified management operations in Amazonia is a significant change, most logging in the region is still predatory, and even operations with Forestry Management Plans (PMFs) approved by IBAMA have heavy impact and poor prospects for sustainability (Cotton and Romine, 1999;Eve et al, 2000). The demand for certified timber is small but growing.…”
Section: Dilemmas Of Forest Management (A) Certification Versus Boycottsmentioning
confidence: 99%
“…Although the increase in certified management operations in Amazonia is a significant change, most logging in the region is still predatory, and even operations with Forestry Management Plans (PMFs) approved by IBAMA have heavy impact and poor prospects for sustainability (Cotton and Romine, 1999;Eve et al, 2000). The demand for certified timber is small but growing.…”
Section: Dilemmas Of Forest Management (A) Certification Versus Boycottsmentioning
confidence: 99%
“…Two studies addressed issues related to health in EIA processes and demonstrate that health has been treated superficially in the case of a logging plan in Pará (Eve et al, 2000) and of a thermal power station in Ceará (Rigotto, 2009).…”
Section: Case Analysismentioning
confidence: 99%
“…By counting the occurrence of the different combinations, the main research fields of the sample of this review could be identified (see Figure 4 and Table S2). Forestry-related studies have set their focus in most cases on a comparison of different forest management strategies [98][99][100][101][102][103][104][105] or specific ecolabels and certification schemes such as FSC and PEFC Forestry-related studies have set their focus in most cases on a comparison of different forest management strategies [98][99][100][101][102][103][104][105] or specific ecolabels and certification schemes such as FSC and PEFC Forestry-related studies have set their focus in most cases on a comparison of different forest management strategies [98][99][100][101][102][103][104][105] or specific ecolabels and certification schemes such as FSC and PEFC [11,[106][107][108][109] in different geographical regions. FWCs are sometimes only partly covered by studies comprising the processes from harvest to the sawmill gate [110], or from harvest to intermediate wood products leaving the sawmill gate (e.g., sawn wood and by-products) [111], or further on to the end consumer wood product leaving the factory gate as an engineered wood product (e.g., plywood, particle boards, fiber boards, laminates, or veneers).…”
Section: Characterization Of the Samplementioning
confidence: 99%